Observations of continuum depression in warm dense matter with x-ray Thomson scattering. - Fletcher, L; Kritcher, A; Pak, A; Ma, T; Döppner, T; Fortmann, C; Divol, L; Jones, O; Landen, O; Scott, H; Vorberger, J; Chapman, D; et al. (American Physical Society, 2014)
Detailed measurements of the electron densities, temperatures, and ionization states of compressed CH shells approaching pressures of 50 Mbar are achieved with spectrally resolved x-ray scattering. Laser-produced 9 keV x-rays probe the plasma during the transient state of three-shock coalescence. High signal-to-noise x-ray scattering spectra show direct evidence of continuum depression in highly degenerate warm dense matter states with electron densities ne>1024  cm-3. The measured densities and temperatures agree well with radiation-hydrodynamic modeling when accounting for continuum lowering in calculations that employ detailed configuration accounting.